1991
DOI: 10.1002/j.1552-4604.1991.tb01906.x
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics and Oral Bioavailability of Hydrocortisone

Abstract: The pharmacokinetics of 20 mg hydrocortisone were studied after IV and oral administration. Endogenous hydrocortisone was suppressed by dexamethasone administration. Hydrocortisone concentrations were measured in plasma and saliva. After IV administration, hydrocortisone was eliminated with a total body clearance of 18 L/hr and a half-life of 1.7 hr. The volume of distribution was 34 L. Oral bioavailability averaged 96%. Absorption was rapid, achieving maximum hydrocortisone levels of 300 ng/mL after 1 hour. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
98
0

Year Published

1993
1993
2015
2015

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 148 publications
(113 citation statements)
references
References 6 publications
15
98
0
Order By: Relevance
“…Another possible factor that may account for this wide variation is that the intravenous dose of hydrocortisone used in the latter study (50 mg) was much higher than the dose used in the study conducted by Derendorf et al (1991) (20 mg) as well as in the present study (15 mg/m 2 ). Our observations are consistent with those of Derendorf et al (1991) who estimated the absolute bioavailability of hydrocortisone to be 95·9% (.. : 19·6).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Another possible factor that may account for this wide variation is that the intravenous dose of hydrocortisone used in the latter study (50 mg) was much higher than the dose used in the study conducted by Derendorf et al (1991) (20 mg) as well as in the present study (15 mg/m 2 ). Our observations are consistent with those of Derendorf et al (1991) who estimated the absolute bioavailability of hydrocortisone to be 95·9% (.. : 19·6).…”
Section: Discussionsupporting
confidence: 92%
“…The pharmacokinetic parameters determined following intravenous administration of hydrocortisone sodium succinate (Solu-Cortef, Pharmacia & Upjohn) in the present study are consistent with those previously reported after oral and intravenous administration of 20 mg hydrocortisone (Hoechst) (Derendorf et al 1991). The latter study was performed in healthy adult volunteers following suppression of the HPA axis by dexamethasone tablets given at 2200 h one day prior to the study.…”
Section: Discussionsupporting
confidence: 89%
“…This dosing regimen, based on that of Young et al (1995), was intended to produce a significant decrease in cortisol levels. In the hydrocortisone condition, 50 mg of hydrocortisone was given orally and was followed 1.5 h later by methamphetamine or placebo (Derendorf et al, 1991). In each of the three premedication conditions (metyrapone, hydrocortisone, or placebo), placebos were substituted for the other drug(s).…”
Section: Methodsmentioning
confidence: 99%
“…Newer estimates of the cortisol production rate (see above) indicate that 15-20 mg total daily HC is required. Unfortunately, HC has a short plasma half-life and patients taking this tablet wake with undetectable cortisol levels, thus achieving peak cortisol levels an hour after dosing (14,62). The pharmacokinetics of 20 mg HC has been studied after i.v.…”
Section: Different Regimens and Dosesmentioning
confidence: 99%